Economic burden of spinal muscular atrophy in the United States: a contemporary assessment. (2nd January 2020) - Droege, Marcus; Sproule, Douglas; Arjunji, Ramesh; Gauthier-Loiselle, Marjolaine; Cloutier, Martin; Dabbous, Omar
Abstract: Aims: To estimate healthcare resource utilization (HRU) and costs among patients with spinal muscular atrophy (SMA) type 1 (SMA1) in real-world practice, overall and among patients treated with nusinersen. As a secondary objective, HRU and costs were estimated among patients with other SMA types (i.e. 2, 3, or 4 combined), overall and among patients treated with nusinersen. Materials and methods: Patients with SMA were identified from the Symphony Health's Integrated Dataverse (IDV) open claims database (September 1, 2016–August 31, 2018) and were classified into four cohorts based on SMA type and nusinersen treatment (i.e. SMA1, SMA1 nusinersen, other SMA, and other SMA nusinersen cohorts). The index date was the date of the first SMA diagnosis after December 23, 2016 or, for nusinersen cohorts, the date of nusinersen initiation. The study period spanned from the index date to the earlier among the end of clinical activity or data availability. Results: Patients in the SMA1 ( n = 349) and SMA1 nusinersen ( n = 45) cohorts experienced an average of 59.4 and 56.6 days with medical visits per-patient-per-year (PPPY), respectively, including 14.1 and 4.6 inpatient days. Excluding nusinersen-related costs, total mean healthcare costs were 137, 627 and 92, 618 PPPY in the SMA1 and SMA1 nusinersen cohorts, respectively. Mean nusinersen-related costs were 191, 909 per-patient-per-month (PPPM) for the first 3 months post-initiation (i.e. loading phase) and 36, 882 PPPM thereafter (i.e. maintenance phase). HRU and costs were also substantial among patients in the other SMA ( n = 5, 728) and other SMA nusinersen ( n = 404) cohorts, with an average of 44.5 and 63.7 days with medical visits PPPY and total mean healthcare costs (excluding nusinersen-related costs) of 49, 175 and 76, 371 PPPY, respectively. Limitations: The database may contain inaccuracies or omissions in diagnoses, procedures, or costs, and does not capture medical services outside of the IDV network. Conclusions: HRU and healthcare costs were substantial in patients with SMA, including in nusinersen-treated patients.